Clinical Management of Patients With B-Cell Depletion Agents to Treat or Prevent Prolonged and Severe SARS-COV-2 Infection: Defining a Treatment Pathway - D’Abramo, Alessandra; Vita, Serena; Maffongelli, Gaetano; Beccacece, Alessia; Agrati, Chiara; Cimini, Eleonora; Colavita, Francesca; Giancola, Maria Letizia; Cavasio, Alessandro; Nicastri, Emanuele; , Spallanzani COVID-19 Case Investigation Team; Corpolongo, Angela; et al. (Frontiers in Immunology, 2022)
Introduction Immunocompromised patients with B-cells depletion agents are at risk for persistence and/or severe SARS-COV-2 infection. We describe a case series of 21 COVID-19 patients under B cell depletion therapy, mostly treated with a combined therapy based on intravenous remdesevir (RDV) and steroid associated with SARS-CoV-2 monoclonal antibodies against Spike glycoprotein and/or hyper-immune convalescent plasma. Methods This is a single-centre longitudinal study. We retrospectively enrolled a total number of 21 B-cell depleted consecutive hospitalized patients with COVID-19 at the Lazzaro Spallanzani National Institute for Infectious Diseases, Rome, Italy, from November 2020 to December 2021. Demographic characteristics, medical history, clinical presentation, treatment, adverse drug reactions, clinical and virological outcome were collected for all patients. In a subgroup, we explore immune T cells activation, T cells specific anti-SARS-COV-2 response and neutralizing antibodies. Results Twenty-one inpatients with B-cell depletion and SARS-COV-2 infection were enrolled. A median of 1 B cells/mm3 was detected. Eighteen patients presented hypogammaglobulinemia. All patients presented interstitial pneumonia treated with intravenous RDV and steroids. Sixteen patients were treated with monoclonal antibodies against SARS-CoV-2 Spike protein, four patients were treated with SARS-CoV-2 hyper-immune convalescent plasma infusion, and three patients received both treatments. A variable kinetic of T cell activation returning to normal level at day 30 after immunotherapy infusion was observed. All treated patients recovered. Conclusion In COVID-19 immunosuppressed subjects, it is mandatory to establish a prompt, effective and combined multi-target therapy including oxygen, antiviral, steroid and antibody-based therapeutics, tailored to the patient's clinical needs.